Guidelines for nurse practitioners in gynecologic settings - Hawkins, Joellen Watson (Springer Publishing Company, LLC, 2016)
The 11th edition of this classic guide for assessment and management of common gynecologic conditions by advanced practice nurses is updated with cutting-edge topics, new evidence-based guidelines, and current patient teaching materials to enhance excellence in clinical practice. This edition features a completely updated chapter on the well-woman annual exam, including issues about the care of older women, and extensive revisions throughout regarding contraceptive methods, CAMs, medical abortion, HIV/AIDS, HPV screening and vaccine recommendations, and much more.